Validation of a screening tool for labor and sex trafficking among emergency department patients. Issue 5 (12th October 2021) - Chisolm‐Straker, Makini; Singer, Elizabeth; Strong, David; Loo, George T.; Rothman, Emily F.; Clesca, Cindy; d'Etienne, James; Alanis, Naomi; Richardson, Lynne D.
Abstract: Objective: Patients with labor and sex trafficking experiences seek healthcare while and after being trafficked. Their trafficking experiences are often unrecognized by clinicians who lack a validated tool to systematically screen for trafficking. We aimed to derive and validate a brief, comprehensive trafficking screening tool for use in healthcare settings. Methods: Patients were randomly selected to participate in this prospective study based on time of arrival. Data collectors administered 5 dichotomous index questions and a reference standard trafficking assessment tool that requires 30 to 60 minutes to administer. Data collection was from June 2016 to January 2021. Data from patients in 5 New York City (NYC) emergency departments (EDs) were used for tool psychometric derivation, and data from patients in a Fort Worth ED were used for external validation. Clinically stable ED adults (aged ≥18 years) were eligible to participate. Candidate questions were selected from the Trafficking Victim Identification Tool (TVIT). The study outcome measurement was a determination of a participant having a lifetime experience of labor and/or sex trafficking based on the interpretation of the reference standard interview, the TVIT. Results: Overall, 4127 ED patients were enrolled. In the derivation group, the reference standard identified 36 (1.1%) as positive for a labor and/or sex trafficking experience. In the validation group, 12 (1.4%) were positive by the reference standard. Rapid Appraisal for Trafficking (RAFT) is a new 4‐item trafficking screening tool: in the derivation group, RAFT was 89% sensitive (95% confidence interval [CI], 79%–99%) and 74% specific (95% CI, 73%–76%) and in the external validation group, RAFT was 100% sensitive (95% CI, 100%–100%) and 61% specific (95% CI, 56%–65%). Conclusions: The rapid, 4‐item RAFT screening tool demonstrated good sensitivity compared with the existing, resource‐intensive reference standard tool. RAFT may enhance the detection of human trafficking in EDs. Additional multicenter studies and research on RAFT's implementation are needed.